2021
DOI: 10.1371/journal.pone.0248143
|View full text |Cite
|
Sign up to set email alerts
|

Community surveillance and response to maternal and child deaths in low- and middle-income countries: A scoping review

Abstract: Background Civil registration and vital statistics (CRVS) systems do not produce comprehensive data on maternal and child deaths in most low- and middle-income countries (LMICs), with most births and deaths which occur outside the formal health system going unreported. Community-based death reporting, investigation and review processes are being used in these settings to augment official registration of maternal and child deaths and to identify death-specific factors and associated barriers to maternal and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Priority setting in health requires robust and timely knowledge on the burden of diseases and mortality to enable efficient resource allocation. While many low- and middle-income countries (LMICs) have built well-functioning civil registration and vital statistics (CRVS) system with good coverage, in many countries, comprehensive systems do not exist [ 1 , 2 ]. There is a drive towards better civil registration system availability and quality globally to ensure better informed decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Priority setting in health requires robust and timely knowledge on the burden of diseases and mortality to enable efficient resource allocation. While many low- and middle-income countries (LMICs) have built well-functioning civil registration and vital statistics (CRVS) system with good coverage, in many countries, comprehensive systems do not exist [ 1 , 2 ]. There is a drive towards better civil registration system availability and quality globally to ensure better informed decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are fewer voices advocating for the involvement of the community in priority setting. Community members have limited roles in setting local health priorities or even being recognised as active agents who should be consulted in setting the agenda [ 2–4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the potential of engaging CHWs in timely local data collection and response in LMICs, there have been questions about the quality and completeness of data reported by them for effectively evaluating program and health outcomes. A recent scoping review suggests that community-based vital events reporting is promising but tends to be sub-optimal in data quality and completeness [ 14 ]. Studies in Mali, Ethiopia, and Malawi, conducted by the ‘Real-Time Monitoring of Under-Five Mortality’ group, found that vital events data collected routinely by CHWs varied in quality and completeness to accurately assess mortality rates at scale.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential of engaging CHWs in timely local data collection and response in LMICs, there have been questions about the quality and completeness of data reported by them for effectively evaluating program and health outcomes. A recent scoping review suggests that community-based vital events reporting is promising but tends to be sub-optimal in data quality and completeness (13). Studies in Mali, Ethiopia, and Malawi, conducted by the 'Real-Time Monitoring of Under-Five Mortality' group, found that vital events data collected routinely by CHWs varied in quality and completeness to assess mortality rates accurately at scale.…”
Section: Introductionmentioning
confidence: 99%